Can bioluminescence resonance energy transfer be used to elucidate structural and binding information about the ABCG2 transporter? - Morris, Joseph (2022)
ATP binding cassette G2 (ABCG2) is a multidrug transporter involved in cancer cell resistance to chemotherapeutics. Uncovering ABCG2 structural and binding information and screening for potential inhibitors is crucial for increasing chemotherapy effectiveness and improving cancer prognoses. The present study examines the potential for bioluminescence resonance energy transfer (BRET) to report on ABCG2: substrate interactions, transporter conformation, and substrate specificity. Three NanoLuc-tagged mutant ABCG2 isoforms designed to alter substrate affinity and specificity were generated and expressed in HEK293T cells and membrane suspensions. NanoBRET assays were carried out in cells and membranes with a concentration range of fluorescent substrates mitoxantrone and rhodamine 123, sometimes in the presence of ABCG2 inhibitor Ko143 and a range of additives. NanoBRET successfully reported on binding of rhodamine 123 by ABCG2 through positive dose-response, however nonspecific BRET effects and/or low affinity substrates prevented the transporter from saturating. This bystander BRET effect appeared to mask differences between ABCG2 constructs, and the effect of Ko143. Therefore, further research with higher affinity ligands or substrates alongside more comparable control cell lines in parallel is required to fully evaluate BRET with ABCG2.